Feminist Cyberlaw - Meg Leta Jones (University of California Press, 2024)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. This vibrant and visionary reimagining of the field of cyberlaw through a feminist lens brings together emerging and established scholars and practitioners to explore how gender, race, sexuality, disability, class, and the intersections of these identities affect cyberspace and the laws that govern it. It promises to build a movement of scholars whose work charts a near future where cyberlaw is informed by feminism.